Regional Differences in Penetration of the Protein Stabilizer Trimethoprim (TMP) in the Rat Central Nervous System - Ineichen, Benjamin V.; Di Palma, Serena; Laczko, Endre; Liddelow, Shane A.; Neumann, Susanne; Schwab, Martin E.; Mosberger, Alice C. (Frontiers in Molecular Neuroscience, 2020)
Regulating gene expression at the protein level is becoming increasingly important for answering basic questions in neurobiology. Several techniques using destabilizing domains (DD) on transgenes, which can be activated or deactivated by specific drugs, have been developed to achieve this goal. A DD from bacterial dihydrofolate reductase bound and stabilized by trimethoprim (TMP) represents such a tool. To control transgenic protein levels in the brain, the DD-regulating drugs need to have sufficient penetration into the central nervous system (CNS). Very limited information is available on TMP in the CNS following systemic injection. Here we performed a pharmacokinetic study on the penetration of TMP into different CNS compartments in the rat. We used mass spectrometry to measure TMP concentrations in serum, cerebrospinal fluid (CSF) and tissue samples of different CNS regions upon intraperitoneal TMP injection. We show that TMP quickly (within 10 min) penetrates from serum to CSF through the blood-CSF barrier. TMP also shows quick penetration into brain tissue but concentrations were an order of magnitude lower compared to serum or CSF. TMP concentration in spinal cord was lower than in any other analysed CNS area. Nevertheless, effective levels of TMP to stabilize DDs can be reached in the CNS with half-lives around 2 hours. These data show that TMP has good and fast penetration properties into the CNS and is therefore a valuable ligand for precisely controlling protein expression in the CNS in rodents.